SOCIALIZATION AND TOURISM AWARENESS TRAINING FOR MANAGERS AND RESIDENTS OF COMMUNITIES AROUND AROSBAYA CRETACEOUS TOURISM OBJECT MADURA - Upik Dyah Eka Noviyanti; Nuruddin Nuruddin (Darmabakti Cendekia: Journal of Community Service and Engagements, 2020)
Background: Arosbaya Limestone Hill has now become one of the alternative developing tourist attractions in Madura. The shape of the hill that has sculptures from the rest of the limestone quarry with unique shapes and the red color of the hill blushed into a uniqueness that invited many tourists to this destination. Besides that, its location is easily accessible and not far from other tourist destinations, namely the grave religious site of the Bangkalan Kings “Mother’s Tears” which incidentally are already well-known making the potential of this destination developed quite large. Purpose: The purpose of this activity is to increase the understanding and ability of both managers and residents around the Arobi Kapur Hill attractions in Berbeluk Village Arosbaya District Bangkalan Madura Regency on how to manage a tourist destination. Methods: awareness raising and tourism awareness training in the form of awareness of tourism awareness concepts and Sapta Pesona Wisata, tourism management training and excellent service. Results: From the results of the socialization and training, the manager and the community around the Bukit Kapor Arosbaya tourism object can get attention and gain knowledge and skills regarding aspects in the management and management of attractions. Conclusion: Partners get increased knowledge and skills in managing a destination. So that his hope through this program creates economic independence of citizens, especially young people through the field of tourism, the availability of new jobs for residents, and the availability of sustainable management of attractions.